2007
DOI: 10.1093/ps/86.3.488
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Glutamine and Vitamin E on the Morphometry of the Intestinal Mucosa in Broiler Chickens

Abstract: The objective of this experiment was to evaluate the influence of Gln and vitamin E (VE) supplementation in the diet of broiler chickens (Cobb-Vantress) on the morphometry of the intestinal mucosa. The design was completely randomized in a 2 x 3 (VE x periods of administering Gln) factorial arrangement. The levels of VE used were 10 and 500 mg/kg of diet and 3 periods of administering (1%) Gln-supplemented starter diet (for the first 7 or 14 d of life or for no added Gln), totaling 6 treatments with 5 replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
51
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 17 publications
20
51
1
8
Order By: Relevance
“…In the present study, intestinal morphometry results corroborated the observations of Maiorka et al (2000), Yi et al (2005) and Murakami et al (2007), who found an improvement in the morphometric characteristics of the intestinal mucosa, both in the duodenum and in the jejunum during the rearing period in broilers fed diets supplemented with glutamine, whether submitted to some form of injury or not.…”
Section: Sources Of Trophic Action On Performance and Intestinal Morpsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, intestinal morphometry results corroborated the observations of Maiorka et al (2000), Yi et al (2005) and Murakami et al (2007), who found an improvement in the morphometric characteristics of the intestinal mucosa, both in the duodenum and in the jejunum during the rearing period in broilers fed diets supplemented with glutamine, whether submitted to some form of injury or not.…”
Section: Sources Of Trophic Action On Performance and Intestinal Morpsupporting
confidence: 92%
“…The author observed greater body weight gain at 21 and 28 days of age for the non-vaccinated birds relative to the vaccinated birds, suggesting an effect of vaccination per se on the integrity of the intestinal mucosa, influencing intestinal development. However, Maiorka et al (2000) and Murakami et al (2007) did not observe any significant differences in the performance of broilers supplemented with 1% glutamine throughout the entire rearing period.…”
Section: Sources Of Trophic Action On Performance and Intestinal Morpmentioning
confidence: 89%
“…A suplementação de L-glutamina na dieta de suínos e aves tem sido utilizada com resultados positivos em seu desempenho, prevenindo a atrofia das vilosidades do jejuno de leitões que receberam dietas com 1% de L-glutamina (Wu et al, 1996), melhorando a eficiência alimentar (Kitt et al, 2001), o ganho de peso, o desenvolvimento da mucosa intestinal de frangos de corte (Murakami et al, 2007) e a taxa de eficiência proteica e aumentando a altura das vilosidades intestinais da carpacomum (Cyprinus carpio) (Yan & Qiu-Zhou, 2006). O conhecimento da mucosa intestinal dos peixes é importante para fornecer informações para os estudos de nutrição, de forma a atender às exigências nutricionais para adequado desempenho e saúde dos peixes.…”
Section: Introductionunclassified
“…Neste estudo, aos sete dias de idade foi possível verificar a ação da glutamina e ácido glutâmico nos segmentos do duodeno e íleo com aumento significativo na altura das vilosidades e profundidade das criptas (Quadro 4), corroborando os de outros autores que também verificaram efeitos benéficos da glutamina sobre o desenvolvimento da mucosa intestinal na primeira semana de vida de aves alimentadas com dieta suplementada com glutamina (Maiorka et al 2000, Sakamoto et al 2005, Bartell & Batal 2007, Murakami et al 2007, aumentando a capacidade funcional da mesma, o que pode propiciar melhor desempenho das aves por meio da maior capacidade de digerir e absorver os nutrientes da dieta. Quanto à maior profundidade de criptas na região do duodeno para o tratamento DC + Vacina nesta fase de criação, este pode ter ocorrido em função da vacina contra coccidiose, aumentando a proliferação das células da cripta na tentativa de reparar os possíveis danos causados pela vacina nas vilosidades intestinais.…”
Section: Histomorfometria Da Mucosa Intestinalunclassified